Evaluation of the effect of hydroalcoholic and flavonoid-enriched extracts of Dracocephalum kotschyi on indomethacin-induced gastric ulcer in rats - Mohsen Minaiyan; Hassan Sadraei; Iman Yousefi; Sayed-Ebrahim Sajjadi; Ardeshir Talebi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Dracocephalum kotschyi (Zaringiah) is a fragrant wild medicinal plant found in Iran. Traditionally, it is used for the treatment of rheumatism, asthma, and gastrointestinal ailments. So far no investigation has been done on the beneficial or side effects of D. kotschyi on peptic ulcer. Therefore, this research was performed to find out whether D. kotschyi extract would induce peptic ulcer or could alleviate existing peptic ulcer. Experimental approach: Effect of hydroalcoholic (DKHE) and flavonoid extracts (DKFE) of D. kotschyi were determined in normal or indomethacin-induced gastric ulcer rats (n = 6) and compared with the vehicle and ranitidine treated controls. All the treatments were carried out orally and 24 h later the stomach mucus was visually examined for peptic ulcers. A section of the stomach was taken for microscopic histopathological examinations while another section of the stomach was used for measurement of myeloperoxidase (MPO) and malondialdehyde (MDA) activities. Findings/Results: Oral administration of the DKHE and DKFE alone, did not cause any sign of gastric ulcer induction. The D. kotschyi extracts not only didn't aggravate the induced ulcer but also significantly prevented the severity of gastric ulcer induction by indomethacin. In addition, DKHE and DKFE inhibited MPO (up to 58.2%) and MDA (up to 44.2%) activities indicating their anti-inflammatory and antioxidant potential action on the stomach-induced ulcer. Conclusion and implication: Usage of D. kotschyi extracts is not associated with gastric ulcer induction and its co-administration with NSAIDs would be beneficial for controlling both the inflammation and preventing gastric ulcer in diseases such as rheumatism.